2016
DOI: 10.1093/icesjms/fsw171
|View full text |Cite
|
Sign up to set email alerts
|

No effect of high pCO2 on juvenile blue crab, Callinectes sapidus, growth and consumption despite positive responses to concurrent warming

Abstract: Future climate scenarios predict increases in both ocean temperature and dissolved carbon dioxide (pCO2) over the next century. Calcifying invertebrates, which depend on specific conditions of temperature and carbonate chemistry for many processes, may be especially affected by these changes. In our study, juvenile blue crab, Callinectes sapidus, were exposed to one of four temperature/pCO2 treatments (ambient/low, ambient/high, high/low, and high/high) for two complete molts. Our study is the first to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…This study supplements the growing body of knowledge on the general impact of climate stressors on estuarine crustaceans. It complements other recent work that has quantified the effects of increased temperature and pCO 2 on the growth and food consumption (Glandon & Miller 2017) and shell properties (Glandon et al 2018) of juvenile blue crabs.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This study supplements the growing body of knowledge on the general impact of climate stressors on estuarine crustaceans. It complements other recent work that has quantified the effects of increased temperature and pCO 2 on the growth and food consumption (Glandon & Miller 2017) and shell properties (Glandon et al 2018) of juvenile blue crabs.…”
Section: Introductionsupporting
confidence: 62%
“…Here, oxygen consumption rates of juvenile blue crabs from the mesohaline Chesapeake Bay were quantified in response to two key climate stressors (increased temperature and pCO 2 ). Treatment levels of temperature and pCO 2 were chosen to reflect current and future predicted climate conditions for the mesohaline Chesapeake Bay by the year 2100 (see Glandon & Miller 2017). The juvenile life stage was examined because of its role in regulating overall crab population dynamics (Miller 2001) and because juveniles are the earliest life stage to live entirely in the estuary (prior development occurs in marine waters).…”
Section: Introductionmentioning
confidence: 99%
“…Another commercially-important inhabitant is the Atlantic blue crab, Callinectes sapidus. When the ambient pCO 2 was raised from 800 to 8,000 µatm, juvenile blue crabs showed no sensitivity to the duration of the intermolt period or to food consumption rate (Glandon and Miller, 2017). Additional studies using the same pCO 2 changes showed small but significant changes in the high-magnesium calcite weight in the carapace of juvenile blue crabs and an increase in magnesium content (Glandon et al, 2018).…”
Section: The Vulnerable Organisms and Ecosystems Of The Us Southeastmentioning
confidence: 89%
“…These investigations have usually found that temperature has a larger impact on the biology of the studied species than acidification (e.g. Wood et al 2010, Noisette et al 2014, Collard et al 2016, Zhang et al 2016, Glandon & Miller 2017, Karelitz et al 2017.…”
Section: Ocean Acidification and Organismal Responsesmentioning
confidence: 99%